1991
DOI: 10.1111/j.1432-1033.1991.tb16355.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ ionophore A23187 and thrombin inhibit the pertussis‐toxin‐induced ADP‐ribosylation of the α‐subunit of the inhibitory guanine‐nucleotide‐binding protein and other proteins in human platelets

Abstract: Inhibitory guanine-nucleotide-binding proteins (Gi proteins) are substrates for pertussis toxin and the decreased pertussis-toxin-dependent ADP ribosylation of Gi proteins upon prior specific hormonal stimulation of cells is thought to reflect the receptor-mediated activation of Gi proteins, leading to their subsequent dissociation into ai and p/y subunits. In the present study, the effect of various platelet stimuli on the subsequent pertussis-toxindependent ADP ribosylation of the a subunit of Gi (Gi,) in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In view of this and to gain an insight into the biochemical mechanisms associated with the activation of PKC under oxidant-triggered condition caused by t-buOOH in bovine pulmonary artery endothelial cells, we tested the hypothesis that t-buOOH-mediated activation of an aprotinin-sensitive protease plays a crucial role in activating PKC and subsequently stimulating cPLA 2 activity in the cell membrane, and AA release from the cells. Because a previous study indicated that pretreatment of pertussis toxin in some cells inhibits stimulation of AA release caused by different stimulants (Clark et al 1986;Sies et al 1991), we also determined whether pertussis toxin pretreatment could prevent t-buOOH-induced cPLA 2 activity and AA release in the cells. Our results suggest that treatment of bovine pulmonary artery endothelial cells with t-buOOH stimulates an aprotinin-sensitive protease activity, which activates PKCα and that subsequently phosphorylates 41-kDa α-subunit of Gi (Giα), leading to stimulation of cPLA 2 activity in the endothelial cell membrane and subsequently AA release from the cells.…”
mentioning
confidence: 99%
“…In view of this and to gain an insight into the biochemical mechanisms associated with the activation of PKC under oxidant-triggered condition caused by t-buOOH in bovine pulmonary artery endothelial cells, we tested the hypothesis that t-buOOH-mediated activation of an aprotinin-sensitive protease plays a crucial role in activating PKC and subsequently stimulating cPLA 2 activity in the cell membrane, and AA release from the cells. Because a previous study indicated that pretreatment of pertussis toxin in some cells inhibits stimulation of AA release caused by different stimulants (Clark et al 1986;Sies et al 1991), we also determined whether pertussis toxin pretreatment could prevent t-buOOH-induced cPLA 2 activity and AA release in the cells. Our results suggest that treatment of bovine pulmonary artery endothelial cells with t-buOOH stimulates an aprotinin-sensitive protease activity, which activates PKCα and that subsequently phosphorylates 41-kDa α-subunit of Gi (Giα), leading to stimulation of cPLA 2 activity in the endothelial cell membrane and subsequently AA release from the cells.…”
mentioning
confidence: 99%
“…In view of this and to gain an insight into the biochemical mechanisms associated with the activation of cPLA 2 under oxidant-triggered condition caused by ONOO - in bovine pulmonary artery endothelial cells, we tested the hypothesis that ONOO - -mediated activation of an aprotinin-sensitive protease plays a crucial role in activating PKC and subsequently stimulating cPLA 2 activity in the cell membrane and AA release from the cells. Since previous studies indicated that pretreatment of pertussis toxin in some cells inhibits AA release caused by different stimulants ( , ), we also determined whether pertussis toxin pretreatment could prevent ONOO - -induced cPLA 2 activity and AA release in the cells. Our results suggest that treatment of bovine pulmonary artery endothelial cells with the oxidant ONOO - stimulates an aprotinin-sensitive protease activity, which activates PKCα and that subsequently phosphorylates the 41 kDa α-subunit of G i (G i α) leading to stimulation of cPLA 2 activity in the endothelial cell membrane and subsequently AA release from the cells.…”
mentioning
confidence: 99%